Optimalisasi Kurikulum Modifikasi untuk Anak Tunagrahita di Sekolah Luar Biasa - Muslimah, Hanif; Nugraha, Nurcahyati; Minsih, Minsih (Journal Of Education And Teaching Learning (JETL), 2025)
Children with intellectual disabilities often face challenges in gaining access and absorbing information in conventional learning environments. Therefore, adapting the curriculum becomes an urgent need to meet their unique needs. This research aims to explain in detail the optimization of curriculum modifications in the context of Special Schools (SLB) at SLB C YPSLB Surakarta to improve the learning of mentally retarded children. This research method uses qualitative descriptive research and data collection by conducting observations, interviews and documentation to collect qualitative data. The research results showed that curriculum modifications at SLB C YPSLB Surakarta took the form of changes to the material content and learning process to ensure education was adapted to students' needs and abilities. Efforts to increase curriculum accessibility by improving children's skills and directing them to the agricultural and culinary fields ensure that students with intellectual disabilities have equal opportunities to develop their potential and prepare for an independent and productive future.